Bureaucratic Oppression: Its Causes and Cures - Edward L. Rubin (Washington University Law Review, 2012)
The purpose of this Article is to expand consideration of the problems involved in the interactions between government and individuals, and to explore potential solutions to those problems, in the same manner that recent legal scholarship has expanded consideration of the problems and potential solutions involved in government policymaking. Because the topic is so vast, it is best approached by considering specific types of interactions between the government and individuals. This Article will focus on interactions that are potentially oppressive. The paradigmatic case, and the image that might most quickly spring to mind, is the treatment of individuals applying for government benefits or licenses. But the problem extends to a much broader range of interactions, including the treatment of business enterprises by regulatory agencies, the treatment of government grantees by funding agencies, the treatment of individuals by protective services like police or firefighters, and the treatment of individuals in government institutions, whether beneficial or restrictive. Of course, each of these situations has distinctive features that merit specific and detailed analysis. Thus, a general discussion of this vast topic is necessarily of a preliminary nature. Part I of the Article discusses the sources of bureaucratic oppression and identifies four such sources: status differences, stranger relations, institutional pathologies, and divergent incentives. Part II explores four solutions to the problem of bureaucratic oppression that have been proposed and in some cases implemented. The first two—the judicial solution of due process and the legislative solution of ombudspersons—involve actors external to the administrative system. The second two—the management theory solution of client-centered administration and the microeconomic solution of market simulating mechanisms—are internal to that system. Because of the limitations of these various solutions, Part III proposes an additional solution, described as a collaborative monitor. This monitor would be an agency of the legislature that could bring the issue of oppressiveness to an administrative agency’s attention and then work collaboratively with that agency to resolve or ameliorate the problem.
Keywords: bureaucracy; bureaucratic oppression; government policymaking; divergent incentivesindividuals; status differences; stranger relations; institutional pathologies